Genomic attributes and characterization of novel exopolysaccharide-producing bacterium Halomonas piscis sp. nov. isolated from jeotgal - Bora Kim; Ah-In Yang; Ah-In Yang; Hae-In Joe; Ki Hyun Kim; Hanna Choe; Sung-Hong Joe; Sung-Hong Joe; Min Ok Jun; Na-Ri Shin (Frontiers in Microbiology, 2023)
Halophilic bacterial strains, designated SG2L-4T, SB1M4, and SB2L-5, were isolated from jeotgal, a traditional Korean fermented food. Cells are Gram-stain-negative, aerobic, non-motile, rod-shaped, catalase-positive, and oxidase-negative. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that strain SG2L-4T is closely related to Halomonas garicola KACC 18117T with a similarity of 96.2%. The complete genome sequence of strain SG2L-4T was 3,227,066 bp in size, with a genomic G + C content of 63.3 mol%. The average nucleotide identity and digital DNA–DNA hybridization values between strain SG2L-4T and H. garicola KACC 18117T were 90.5 and 40.7%, respectively. The optimal growth conditions for strain SG2L-4T were temperatures between 30 and 37°C, a pH value of 7, and the presence of 10% (w/v) NaCl. The polar lipids identified included diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, an unknown phospholipid, an unknown glycolipid, and an unknown polar lipid. The major cellular fatty acids were C16:0, summed features 8 (C18:1ω6c and/or C18:1ω7c), C19:0 cyclo ω8c, and summed features 3 (C16:1ω6c and/or C16:1ω7c). The predominant respiratory quinone was ubiquinone with nine isoprene units (Q-9). Based on the phenotypic, genotypic, and chemotaxonomic results, strain SG2L-4T represents a novel species within the genus Halomonas, for which the name Halomonas piscis sp. nov. is proposed. The type strain is SG2L-4T (=KCTC 92842T = JCM 35929T). Functional annotation of the genome of strain SG2L-4T confirmed the presence of exopolysaccharide synthesis protein (ExoD) and capsular polysaccharide-related genes. Strain SG2L-4T also exhibited positive results in Molisch’s test, indicating the presence of extracellular carbohydrates and exopolysaccharides (EPS) production. These findings provide valuable insights into the EPS-producing capabilities of H. piscis sp. nov. isolated from jeotgal, contributing to understanding its potential roles in food and biotechnological applications.